“I was forced into it”: The continued violation of widows from the Luo community of Kenya through sexual cleansing rituals - Munala, Leso; Mwangi, Esther; Harris, Margaret; Okunna, Nene; Yewhalawork, Bethlehem; Ong'ombe, Maureen (Frontiers in Global Women's Health, 2022)
Sexual cleansing is part of the social transition process for widows to become eligible to remarry after the death of her husband. This ritual is conducted to cleanse the widow of evil spirits resulting from the death of her husband. This qualitative study explored the sexual cleansing ritual in the Luo community in southwest Kenya. This paper aims to examine the widows' perceptions of the social constructs surrounding the practice of the sexual cleansing ritual that maintains its continued existence in this community. Twenty-seven face-to-face in-depth interviews were conducted with widows who had undergone sexually cleansing. Data was analyzed using conventional content analysis. Three main themes emerged in the exploration of the social construction of the sexual cleansing ritual of widows. The findings therein highlight the precarious situation of widows and the need for social support services for women who have been sexually cleansed.